Analisis Perlindungan Konsumen dalam Kasus Produk Skincare yang Mengandung Merkuri - Dwi Lestari; Talita Dhea Alsabilla; Iyut Rosmita Putri; Sintong Arion Hutapea (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This research studies consumer protection against the dangers of using mercury skincare for health, so that consumers, especially women, can be more careful in choosing and using skincare. Mercury is an ingredient that is often added to skincare ingredients that function to produce white facial skin quickly. Mercury can flow through the blood throughout the body which can cause death. However, many consumers among women are more easily tempted to use mercury-based skincare because they see instant results. Skincare made from mercury is strictly prohibited from use because of its content which can cause damage to organs and nerves of the body by a substance such as chemicals and cause abnormalities in the functioning of the health system. The purpose of this study is to analyse consumer protection against cases of skincare products containing mercury such as the case of lightening cream and night cream brand MH.